Fluorescence Resonance Energy Transfer in Quantum Dot-Protein Kinase Assemblies - Yildiz, Ibrahim (Hindawi Publishing Corporation, 2007)
In search of viable strategies to identify selective inhibitors of protein kinases, we have designed a binding assay to probe the interactions of human phosphoinositide-dependent protein kinase-1 (PDK1) with potential ligands. Our protocol is based on fluorescence resonance energy transfer (FRET) between semiconductor quantum dots (QDs) and organic dyes. Specifically, we have expressed and purified the catalytic kinase domain of PDK1 with an N-terminal histidine tag [His(6)-PDK1(ΔPH)]. We have conjugated this construct to CdSe-ZnS core-shell QDs coated with dihydrolipoic acid (DHLA) and tested the response of the resulting assembly to a molecular dyad incorporating an ATP ligand and a BODIPY chromophore. The supramolecular association of the BODIPY-ATP dyad with the His(6)-PDK1(ΔPH)-QD assembly encourages the transfer of energy from the QDs to the BODIPY dyes upon excitation. The addition of ATP results in the displacement of BODIPY-ATP from the binding domain of the His(6)-PDK1(ΔPH) conjugated to the nanoparticles. The competitive binding, however, does not prevent the energy transfer process. A control experiment with QDs, lacking the His(6)-PDK1(ΔPH), indicates that the BODIPY-ATP dyad adsorbs nonspecifically on the surface of the nanoparticles, promoting the transfer of energy from the CdSe core to the adsorbed BODIPY dyes. Thus, the implementation of FRET-based assays to probe the binding domain of PDK1 with luminescent QDs requires the identification of energy acceptors unable to interact nonspecifically with the surface of the nanoparticles.